Analisis Dampak Pandemi Covid-19 terhadap Perubahan Fokus Corporate Social Responsibility (CSR) pada Hennes & Mauritz Co., Ltd - Linda Nurwulan Apriliani; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to analyze: 1) The level and quality of Corporate Social Responsibility (CSR) disclosure before and during COVID-19 of Hennes & Mauritz Co., Ltd for the year 2016-2021 based on the GRI 2021 Standard, 2) Differences in focus changes of CSR before and during COVID-19 of Hennes & Mauritz Co., Ltd for the year 2016-2021 based on the GRI 2021 Standards. This is a interpretative qualitative research using Sustainability Report of Hennes & Mauritz Co., Ltd for the year 2016-2021. Data for this study were secondary data were analyzed using content analysis technique. The result show that: 1) Based on the results of content analysis on the level of disclosure of economic, environmental and social indicator on the sustainability report of Hennes & Mauritz Co., Ltd there has been an increase in the number of level and quality of disclosure during COVID-19, 2) There is a change in the focus of disclosure of CSR before and during the COVID-19. H&M shifted the focus of CSR from environmental(300) to economic performance (201) and occupational health and safety (403).